Nursing Students Readiness Through Clinical Learning - Sondang Ratnauli Sianturi; Lia Natalia (Journal of Nursing Science Update (JNSU), 2021)
Students’ experiences in doing clinical learning are a challenge in themselves where studnets interact directly with patients and face the changes that occur. Students are prepared in various aspects to deal with learning in clinics where students contact with patients. The phenomenon that occurs is students are not confident to practice and learn cases in clinic, fear of the tasks and responsibilities given. The purpose of this study is to describe of nursing student readiness when practice in clinical setting at the Nursing Institution in Jakarta. This research method is a quantitative method with a correlative design with 219 samples (nursing students). The measuring instrument used in this study is by using the CLES questionnaire, motivation and anxiety faced by students. The results showed that the RMSEA value is 0.000, which means that the fit of the model is good or good fit and 90% internal confidence, and there is an influence from the environment (p value 0,000), motivation (p value 0,000) and anxiety factors (p value 0,000) to the readiness students doing clinical learning. Therefore, to get good service quality in nursing education, collaboration between health care and education is very important to create a conducive environment for students to conduct clinical learning.